Impact of cardiovascular autonomic neuropathy in gastroesophageal reflux diseases (GERD)– A clinical study - THILIP KUMAR G; JAMUNA RANI R; K.L. SATHISH KUMAR; LALITHAMBIGAI G; MARUTHY K N; QAIRUNNISA (International Journal of Pharma and Bio Sciences, 2019)
Gastro esophageal reflux diseases (GERD) is an abnormal reflux of gastric content in esophagus or beyond in to the oral cavity (including larynx) or lungs which produces wide range of troublesome symptoms.The pathophysiology of GERD is more complex, but the most possible mechanism for the reflux diseases is the disturbance of autonomic nervous system. In this study, we aimed to analyze the cardiovascular autonomic neuropathy in normal individuals (control) compared with GERD patients. A case control, age matched study was conducted among 40 controls and 40 GERD patients. A Cardiovascular autonomic neuropathy was assessed by using a non-invasive Ewing’s cardiovascular autonomic function test and Heart Rate Variability (HRV). HRV wasassessed by simple analog amplifier with PC-based sound card (audacity). Data was checked for normality using Kolmogorov Smirnov test. As data was normally distributed, Student ‘t’ test was used to compare the difference between two groups. The level of significance was set at *P<0.05. Heart rate response to deep breathing, immediate standing, valsalava maneuver and blood pressure response to immediate standing and Hand grip test in GERD group showed statistically difference when compared to control group. The time domain parameters SDNN, RMMSD, NN50, pNN50 were statistically significant and decreased in GERD group when compared to control. Frequency domain parameter LF power % and normalized unit showed statistically significant increased in GERD group whereas HF power % and normalized unit and total power showed significant decrease in GERD group when compared to control group. To conclude, GERD group exhibited autonomic dysfunction especially vagal impairment that leads to increase the transient lower esophageal sphincter relaxation.